In vitro culture of Mesocestoides corti metacestodes and isolation of immunomodulatory excretory–secretory products. (20th June 2016) - Vendelova, E.; Hrčková, G.; Lutz, M. B.; Brehm, K.; Nono Komguep, J.
Summary: Cestode‐mediated diseases hold the interesting feature of persisting metacestode larvae dwelling within the host tissues, in the midst of the immune response. Excretory–secretory (ES) products of the metacestode larval stage modulate the host immune response and modify the outcome of the disease. Therefore, isolation and analysis of axenic metacestode ES products are crucial to study their properties. Here, we report the development of a system for long‐term in vitro cultivation of the metacestode of the parasitic cestode Mesocestoides corti (syn. Mesocestoides vogae ). Although feeder cells and host serum supported the early growth of the parasite, long‐term survival was not dependent on host serum or host‐derived factors enabling the collection of parasite released products in serum‐free medium. Functionally, these axenic ES products recapitulated M. corti tetrathyridia's ability to inhibit LPS‐driven IL‐12p70 secretion by dendritic cells. Thus, our new axenic culture system will simplify the identification and characterization of M. corti ‐derived immunomodulatory factors that will indirectly enable the identification and characterization of corresponding factors in the metacestode larvae of medically relevant cestodes such as Echinococcus multilocularis that are not yet amenable to serum‐free cultivation.